Peran Credit Union Stella Maris dalam Penguatan Ekosistem Masyarakat Sipil di Pontianak Kalimantan Barat - Alanuari; Hukma Kaulan Karima (SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
The Credit Union (CU) movement in Pontianak City, West Kalimantan, has long been recognized for its significant role in enhancing the economic well-being of its members. However, its contribution to strengthening civil society dimensions is often overlooked. This study aims to analyze and identify in depth how credit unions play a crucial role in building and reinforcing the foundations of civil society in Pontianak, beyond their primary function as microfinance institutions. Using qualitative data collected in 2019 from the Stella Maris Credit Union in Pontianak, this research reveals that CU functions not only as a provider of inclusive financial access but also as an essential space for economic self-reliance, democratic participation, and social solidarity, all of which are vital elements for strengthening the civil society ecosystem. The findings demonstrate that through cooperative principles and sustainable educational programs, both financial and non-financial, CU has successfully fostered collective awareness, enhanced financial literacy, and promoted a spirit of mutual cooperation among its members. Furthermore, its participatory decision-making mechanism reflects grassroots democratic practices essential to the empowerment of civil society. Thus, the Credit Union has transformed into an agent of social change, empowering communities to act independently and collectively in addressing socio-economic challenges. The implications of this study suggest that Credit Unions should be viewed as an important pillar of civil society in Pontianak and as a potential model for other community-based institutions in Indonesia in building a more independent, empowered, and democratic society.